On Complete Convergence of Moving Average Process for AANA Sequence. (17th May 2012) - Yang, Wenzhi; Wang, Xuejun; Ling, Nengxiang; Hu, Shuhe
Abstract : We investigate the moving average process such that X n = ∑ i = 1 ∞ a i Y i + n, n ≥ 1, where ∑ i = 1 ∞ | a i | < ∞ and { Y i, 1 ≤ i < ∞ } is a sequence of asymptotically almost negatively associated (AANA) random variables. The complete convergence, complete moment convergence, and the existence of the moment of supermum of normed partial sums are presented for this moving average process.